The impact of project-based learning on mathematics interest and self-efficacy among senior high school students - Rahman, Arief Aulia; Usalmy, Nyak Wha; Hernández, César; Refugio, Craig N (Jurnal Elemen, 2025)
This research sought to explore how the Project-Based Learning (PjBL) model affects the learning interest and self-efficacy of eleventh-grade students in Senior High School. Employing a quantitative quasi-experimental design, the study utilized a sample of eleventh-grade students selected through simple random sampling. Data were gathered using questionnaires and observational methods and analyzed using a multivariate analysis of variance (MANOVA) test. The results underscored the notable influence of the PjBL model in enhancing learning interest and self-efficacy. The PjBL approach positively affected these variables in the experimental group of 28 students. The robustness of these results was confirmed by Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root tests, each demonstrating F-values with a significance level of 0.000, well below the threshold of 0.05. Moreover, the Coefficient of determination (R²) revealed that the PjBL model accounted for 73.5% of the variance in learning interest and 90.2% in self-efficacy, with the remaining variance being attributable to other factors not addressed in this study.